Study of Ethnolinguistic-Сultural Features of Zoomorphisms in Scientific Researches - Norkuziyeva Dildora Sheraliyevna (Zien Journals, 2022)
In studies on fictional literature, the ethnolinguistic-cultural characteristics of zoomorphisms are considered one of the least studied areas of scientific research. From the point of view of the current period, such studies are important in the ethnolinguistic-cultural field of literature. This article analyzes and highlights zoomorphisms and their methodological and semantic features in fiction, the role and significance of animal images in the culture and literature of different peoples through examples. Each nation and people uses animal names that are unique in oral speech and works of art, based on their perennial traditions and mentality. These features are also thoroughly analyzed in this article. In order to increase the scale and weight of a work of art, as well as to re-embody it in the eyes of the reader, we can find specific zoomorphisms in the works of different peoples.
Keywords: Zoomorphism; Ethnolinguistic -Cultural; Names Of Animals; Metaphor; Mythical Worldview